Statistical network optimisation of dynamically complex systems. (15th October 2009) - Shamseldin, Ramez Ahmed; Bowling, Shannon R.
The aim of this research is to optimise large-scale network handling capabilities for large system inventories and to implement strategies for the purpose of reducing capital expenses. As computers become more and more networked, it is easier to share files among storage media. In addition, more bandwidth will be consumed by network flow because customers will be connected through networks which will transfer files and data, such as video files (MPEGn, AVI, WMV, etc.) to be viewed at a customer's computer (host).